Health Insurance and Access to Health Care Services in Developing Countries - DOMAPIELLE, MAXIMILLAN KOLBE (Universitas Muhammadiyah Yogyakarta, 2014)
There is growing awareness of the fact that illhealthperpetuates poverty. In order to preventthe negative downward spiral of poverty andillness, developing countries in recent yearsare increasingly implemen ting various modelsof health insurance to increase access tohealth care for poor households. While thereis consistent evidence that health insuranceschemes have caused an increase in accessto health generally, the debate regarding themost appropriate health insurance schemethat suits the poor continues unabated.Drawing on relevant literature this paperadopts a framework for assessing access tohealth care services to explore fourdimensions of access, including: geographicaccessibility, availability, affordability,acceptability of services. The paper arguesthat irrespective of the model of healthinsurance being implemented thesedimensions of access govern the poor and thepoorest household decisions about enrolling ina health insurance scheme and utilizing healthcare services. Policy makers and plannersneed to pay attention to these importantdimensions when making decisions regardinghealth insurance and health care servicesutilization to ensure that the peculiar needs ofthe poor are taken on board.Key words: access, developing countries,health insurance models, universal healthcoverage,